2019
DOI: 10.1002/edm2.68
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diet/exercise and pharmacotherapy to enhance the GLP‐1 levels in type 2 diabetes

Abstract: The rapid rise in the prevalence of type 2 diabetes mellitus (T2DM) poses a huge healthcare burden across the world. Although there are several antihyperglycaemic agents (AHAs) available including addition of new drug classes to the treatment algorithm, more than 50% of patients with T2DM do not achieve glycaemic targets, suggesting an urgent need for treatment strategies focusing on prevention and progression of T2DM and its long‐term complications. Lifestyle changes including implementation of healthy diet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 120 publications
(164 reference statements)
0
12
0
1
Order By: Relevance
“…14 Various studies have demonstrated the benefit of increased GLP-1 expression induced by BAs in type II diabetes and other diseases. 15 Recent research suggests that teneligliptin could prevent obesity by enhancing the function of brown adipose tissue, which may be mediated by BAs, as BAs are known to promote brown adipose activity. 16,17 In the present study, we postulated that teneligliptin could improve BA synthesis.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…14 Various studies have demonstrated the benefit of increased GLP-1 expression induced by BAs in type II diabetes and other diseases. 15 Recent research suggests that teneligliptin could prevent obesity by enhancing the function of brown adipose tissue, which may be mediated by BAs, as BAs are known to promote brown adipose activity. 16,17 In the present study, we postulated that teneligliptin could improve BA synthesis.…”
Section: Introductionmentioning
confidence: 61%
“…DPP-4 rapidly degrades circulating glucagon-like peptide-1 (GLP-1), a gut-derived hormone involved in insulin secretion, metabolism, and satiety. , BAs have been shown to induce the expression of GLP-1 through the activation of G protein-coupled bile acid receptor TGR5, thereby improving glucose metabolism . Various studies have demonstrated the benefit of increased GLP-1 expression induced by BAs in type II diabetes and other diseases . Recent research suggests that teneligliptin could prevent obesity by enhancing the function of brown adipose tissue, which may be mediated by BAs, as BAs are known to promote brown adipose activity. , In the present study, we postulated that teneligliptin could improve BA synthesis.…”
Section: Introductionmentioning
confidence: 69%
“…However, administration of glucose by the mice voluntarily ingesting glucose gels led to lower glucose peaks post administration compared to oral gavage. Although we cannot rule out the possibility of enhanced incretin effects with glucose gels due to chewing, the differences observed are also likely to be associated with the reduced stress of voluntary gel consumption (Fujiwara et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…1) [31]. Neben Insulinen sollte auch der Einfluss anderer glukosesenkender Therapeutika auf postprandiale Glukoseanstiege, die u. a. infolge einer Veränderung der Sekretion von Darmhormonen und/ oder einer Verzögerung der Magenentleerung entstehen, berücksichtigt werden [33].…”
Section: Typ-2-diabetesunclassified